The Mbolo Weki Tradition as Local Wisdom in the Hadith Perspective: A Socio-Cultural Study of the Bima People, Indonesia - Khaerul Bilqalam; Siti Aisyah Kara; Abdul Rahman Sakka (Universitas Negeri Jakarta, 2025)
Local traditions within Muslim communities reflect the internalization of Islamic values in social life. This study examines the Mbolo Weki tradition in Bolo District, Bima Regency, as well as the understanding of prophetic traditions (ḥadīth) related to the values embodied in this practice. Using a qualitative approach with ḥadīth, socio-cultural, and historical perspectives, data were collected through observation, interviews, documentation, and studying classical Islamic texts. Informants included religious leaders, traditional elders, village officials, and community members. The findings indicate that Mbolo Weki, a tradition of cooperation during wedding celebrations, aligns with Islamic values such as consultation (shūrā) and mutual assistance. Although its practice has become more simplified and collective participation has declined, core values like solidarity and kinship remain preserved. This tradition represents a form of local wisdom that reflects the teachings of Prophet Muhammad (peace be upon him) and strengthens social cohesion within the Muslim community of Bima.